Writing and publishing as empowerment in Baker Lake, Nunavut - Driedger, Diane (Études/Inuit/Studies, 2011)
This article examines creative writing, publishing, and empowerment of Inuit adult learners in Baker Lake, Nunavut. I taught a creative writing workshop at Nunavut Arctic College along with the local elders, who taught songs from the Baker Lake area. After the workshop, in February 2006 The Sound of Songs: Stories by Baker Lake Writers, an anthology of the adult learners’ writings, was published and launched at the Baker Lake Community Centre. In the course of the project, the Project Advisory Committee and I examined the meaning of the term “empowerment” in the context of Inuit culture. Each of the nine learners who took part in the workshop published at least one piece in the book. Most of them reported some degree of empowerment through increased confidence in their own writing, through increased respect from community members, especially the elders, and also through learning to be a “real Inuk” from the elders who taught songs from the Baker Lake area. Since most of the learners had not heard the songs before, elders and younger people had an opportunity to understand each other better.